Enhancing landslide predictability: Validating geophysical surveys for soil moisture detection in 2D and 3D scenarios - Bortolozo, Cassiano Antonio [UNESP]; Mendes, Tatiana Sussel Gonçalves [UNESP]; Egas, Harideva Marturano; Metodiev, Daniel; Moraes, Maiconn Vinicius de [UNESP]; Andrade, Marcio Roberto Magalhães de; Pryer, Tristan; Ashby, Ben; Motta, Mariana Ferreira Benessiuti [UNESP]; Simões, Silvio Jorge Coelho [UNESP]; Pampuch, Luana Albertani [UNESP]; Mendes, Rodolfo Moreda; et al. (Elsevier, 2023)
Every year, Brazil grapples with the destructive impact of landslides, typically during the summer season. The National Centre for Monitoring and Alerts of Natural Disasters (Cemaden) places significant emphasis on studying these phenomena to understand their processes and causes more deeply. One key challenge faced in this endeavour is the procurement of geotechnical properties of the soil in high-risk areas, with soil moisture being a crucial factor. Collecting point samples for acquiring these geotechnical parameters is not only costly but also limited in providing a comprehensive two-dimensional or three-dimensional coverage. Therefore, the primary aim of the proposed project is to validate the method of acquiring soil moisture data through geophysical surveys in both 2D and 3D scenarios. Data was gathered from soil moisture stations within Cemaden's network and various collected samples to confirm the results. To generate more controlled yet realistic conditions, a sequence of field infiltration experiments was conducted. The findings, related to the ability of the geoelectric method to define soil moisture, derived from this project form an invaluable foundation for future investigations spearheaded by the Geodynamics Group and its collaborating institutions.
Keywords: Brazil; DC method; Infiltration experiments; Rain simulation; Soil moisture